Melatonin and the Prevention and Management of Delirium: A Scoping Study - Choy, Sin Wei; Yeoh, Aun Chian; Lee, Zhao Zheng; Srikanth, Velandai; Moran, Chris (Frontiers in Medicine, 2018)
Background: The therapeutic benefit of melatonin in the prevention and treatment of delirium is uncertain. Objective: To perform a scoping study to describe the existing literature regarding the use of melatonin and ramelteon in the prevention and treatment of delirium. Methods: We performed a scoping study using the Arksey and O’Malley framework to explore our objective. Two independent panels searched MEDLINE, OVID, EMBASE, PubMed, Google Scholar and Cochrane Library for relevant articles up to November 2017 describing the use of melatonin and ramelteon in the prevention or management of delirium. We extracted relevant summary data from the studies and attempted to draw conclusion regarding benefit. Results: We summarized evidence from 20 relevant articles. There were a total of nine articles: five Randomized Controlled Trials (RCT), two retrospective medical record reviews, one non-randomized observational study and one case report describing the role of either melatonin or ramelteon in preventing delirium. There were a total of 11 studies studying the role of either melatonin or ramelteon in the management of established delirium. None of these were RCT and were predominantly case series and case reports. Four of the five trials studying the effect of melatonin analogues in preventing delirium reported a beneficial effect but study heterogeneity limited any broad recommendations. Similarly, the lack of any well designed trials limits any recommendations regarding the effect of melatonin analogues in treating delirium. Conclusions: Large, well-designed clinical trials are required to explore the potential beneficial effects of melatonin and ramelteon on delirium prevention and management.